CONTRIBUTIONS TO THE STUDY OF THE VIBRATIONS FREQUENCY OF THE DRILL TOOL IN THE PROCESS OF MANUFACTURING THE BRONZE MATERIALS - Cosmin-Mihai MIRIŢOIU; Daniela Florentina TĂRÂŢĂ; Catălin ROŞU; Alexandru STANIMIR; Marius ZAMFIRACHE (Fiabilitate şi Durabilitate)
In this paper we present the experimental testings used to study the vibration of the drill tool, during the drilling of the bronze products. We have used the experimental setup presented in Miriţoiu (2013)[1]. In this paper the vibrations are analyzed during the drilling on the universal lathe machines. The main purpose of to find a correlation between the cutting speed and the frequency of the vibration by using the experimental results and the regression analysis